Analysis of the interaction transcriptome during biotrophic invasion of rice by the blast fungus, Magnaporthe oryzae - Mosquera Cifuentes, Gloria Maria (Kansas State University, 2007)
The hemibiotrophic rice blast fungus Magnaporthe oryzae undergoes complex morphological development throughout its infection cycle. From 8-20 hours after a fungal spore lands on a leaf surface, the fungus differentiates a complex appressorium that punctures the host cuticle. By ~24 hours post inoculation (hpi), the fungus grows inside an epidermal cell as a primary hypha, and by 36 hpi the fungus has differentiated specialized biotrophic invasive hyphae (IH) that are filling the first-invaded cell and moving into neighbor cells. Throughout its life cycle, IH invade living rice cells although invaded cells appear dead when the fungus moves into the next cell. Biotrophic invasion must be mediated by fungal effectors, proteins that pathogens secrete inside live host cells to control them. However, little is known about blast effectors, and the low fungal biomass in early infection stages complicates identification of effector genes, as well as identification of rice genes controlled by effectors. The characterized AVR-Pita effector gene is specifically expressed in planta, but it was not clear how its gene expression pattern changed in different infection stages. We found that AVR-Pita is first expressed around the time of penetration. AVR-Pita is highly expressed in IH developing in asymptomatic tissue from 36 hpi to as late as 7 days post inoculation when lesions are maturing. Using inoculated rice sheaths, we successfully enriched for infected tissue RNA that contained ~20% IH RNA at 36 hpi. We compared IH gene expression to expression in mycelium from pure culture using a whole-genome M. oryzae oligoarray, and we compared infected rice gene expression to expression in mock-inoculated tissue using a rice oligoarray. Rice genes that were induced >50-fold during infection were enriched for genes involved in transferring information from sensors to cellular responses. Fungal genes that were induced >50-fold in IH included known effectors and many IH-specific genes encoding hypothetical secreted proteins that are candidate effectors. Gene knock-out analyses of three putative effector genes failed to show major effects on pathogenicity. Details of the blast interaction transcriptome will provide insights on the mechanisms of biotrophic plant disease.
Keywords: rice blast; gene expression; biotrophic; Magnaporthe; Agriculture, Plant Pathology (0480)